2013
DOI: 10.1039/c3dt32536a
|View full text |Cite
|
Sign up to set email alerts
|

On the role of strong electron correlations in the surface properties and chemistry of uranium dioxide

Abstract: We report density functional calculations of the surface properties and chemistry of UO(2)(111) performed within the generalized gradient approximation corrected with an effective Hubbard parameter (GGA + U within Dudarev's formalism) to account for the strong on-site Coulomb repulsion between U 5f electrons. The variation of the properties of periodic slab models, with collinear ferromagnetic and antiferromagnetic arrangements of the uranium magnetic moments, was investigated while ramping up the effective Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 62 publications
(92 reference statements)
3
21
0
Order By: Relevance
“…The crystal structure was also optimized by adding the Hubbard correction with the parameter, U eff = 4.0 eV, determined by Weck et al 97 for uranium dioxide. The results, given in Table 1, show that the Hubbard correction does not introduce significant changes to the computed crystal structure.…”
Section: Crystal Structurementioning
confidence: 99%
“…The crystal structure was also optimized by adding the Hubbard correction with the parameter, U eff = 4.0 eV, determined by Weck et al 97 for uranium dioxide. The results, given in Table 1, show that the Hubbard correction does not introduce significant changes to the computed crystal structure.…”
Section: Crystal Structurementioning
confidence: 99%
“…Theoretical studies have disagreed as to whether molecular or dissociative adsorption is more energetically favourable on the (111) surface of UO 2 . Skomurski et al [22] and Weck et al [23] both found molecular adsorption to be more favourable, with adsorption energies of c. -0.7 (-0.25 for 1 monolayer (ML)) and -0.8 eV, whilst dissociative adsorption energies were lower with -0.4 (-0.22 for 1 ML) and -0.6 eV for a coverage of ½ ML. More recent studies have found dissociative adsorption to be more favourable at low coverage of ¼ ML, by 0.02 eV [24] and 0.07 eV [25], with an adsorption energy of -1.12 eV [24] and -0.68 eV [25] for dissociative adsorption.…”
Section: Introductionmentioning
confidence: 98%
“…134 The inuence of the Hubbard correction, 148 allowing for a correct description of the strong Coulomb repulsion between electrons in f orbitals, was also evaluated. The introduction of this correction, improving signicantly the description of uranium containing systems in which uranium exists with IV oxidation state, [149][150][151][152][153][154] seems not to be needed for vandenbrandeite as shown in Section 3. In fact, for a numerous set of materials in which uranium exists with VI oxidation state, the standard DFT description provides a reliable description of their structures and properties.…”
Section: Introductionmentioning
confidence: 99%